STUDIES ON THE BINDING BETWEEN STREPTOCOCCAL M PROTEIN AND ANTIBODY - Grey, Howard M. (The Rockefeller University Press, 1962)
A method for detecting type-specific antibody to type 12 β-hemolytic streptococci is described. The method is based on the utilization of a partially purified I(131) labeled streptococcal acid extract and the solubility of this extract in 40 per cent saturated ammonium sulfate as compared to the insolubility of antibody and antigen-antibody complexes at this salt concentration. The salient features of this technique are: (a) When absorbed sera were used, no non-type-specific reaction with antigen occurred. (b) The sensitivity of the system allowed detection of type-specific antibody in hyperimmune antisera that had been diluted 1200-fold. (c) The method does not rely on secondary manifestations of antigen-antibody interaction for the detection of antibody. (d) As little as 0.03 µg of M(12) protein was detected when soluble unlabeled M protein was used to inhibit the reaction between I(131) M(12) protein and anti-M(12) antibody. (e) The kinetics of the reaction between M protein and anti-M antibody can be studied, thereby making information available as to the quality as well as the quantity of antibody produced in this antigen-antibody system.